Identifikasi Kedalaman Muka Air Tanah dan Posisi Akuifer di Kabupaten Tolikara - Frans Polangco Wambena; Alfian Adie Chandra; Dewi Ana Rusim (Jurnal Sipil Terapan, 2024)
Groundwater is dynamic and influenced by a number of natural factors. Geology and geomorphology greatly determine the condition of the soil in an area. The geological structure influences the direction of groundwater movement, the type and thickness of the aquifer. The Karubaga District in Tolikara Regency is an area with a morphology of mountains, hills and valleys so it has the potential for rivers and streams that can be used as a source of raw water. Identification of the depth of the groundwater level in the Karubaga District is carried out using tools in the form of the AIDU Golden Rod (AGR), which is a special geophysical study instrument that provides a detailed vertical picture 300 m into the ground surface to read the resistivity values of rocks and aquifers by measuring the natural electric field